Examining the Influence of Learner Emotion and Motivation on English Vocabulary Acquisition at SMP Nusantara Palangka Raya - Rianti, Nur Pebiy; Baehaqi, Luqman; Mirza, Akhmad Ali (Journal of English Language and Education, 2025)
This research explores the relationship between students' emotions and motivation in relation to vocabulary acquisition in English as a Second Language (L2). Emotions are defined as psychological responses within individuals, while motivation refers to the internal or external drive that influences behavior. Both factors are recognized as key contributors to academic success, particularly in learning English vocabulary. The study involved 36 junior high school students (grades 7–9) at SMP Nusantara Palangka Raya. Data were collected using the DERS questionnaire to measure emotions, the MSLQ to assess motivation, and a vocabulary test to evaluate vocabulary acquisition. Regression and correlation analyses were used to determine the strength and direction of the relationships. The analysis showed no significant relationship between emotions (X1) and vocabulary acquisition (Y), with a regression coefficient of 28.900 and a t-value of 0.034, which was not statistically significant at α=0.05. This suggests that emotional factors may not strongly influence vocabulary outcomes in this sample. On the other hand, motivation (X2) showed a positive regression coefficient of 0.006 and a significant t-value of 2.034, indicating a meaningful relationship between motivation and vocabulary acquisition. The coefficient of determination (R²=0.114) suggests that only 11.4% of the variance in vocabulary acquisition can be explained by the two variables. The correlation coefficient (r=0.380) implies a moderate relationship between the independent variables and the dependent variable. The findings highlight the role of motivation over emotion in vocabulary learning and suggest the need for further research. This study offers valuable insights for educators in developing effective English learning strategies.